2000
DOI: 10.1243/0954411001535480
|View full text |Cite
|
Sign up to set email alerts
|

External ring fixators: An overview

Abstract: External fixation is widely used in the fixation of fractures and limb deformities. The mechanical characteristics of a specific external fixator are major factors in determining the biomechanical environment at a fracture/osteotomy site and, hence, affect the healing process. Although the optimal biomechanical environment for healing of a fracture or an osteotomy is unknown, a specific range of interfragmentary motion exists which promotes healing. It is therefore desirable that the mechanics of an external f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 39 publications
2
53
0
2
Order By: Relevance
“…The resultant fixator exhibited decreased stiffness at higher loads and less axial and bending stiffness when compared to traditional Ilizarov circular external fixators. 28,29 This led to unwanted motion and the fracture site with resultant loss of reduction, non-union and increased pin-site infection rates. [30][31][32][33][34] Conventional circular external fixation, however, has recently emerged as a viable treatment alternative for bicondylar plateau fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resultant fixator exhibited decreased stiffness at higher loads and less axial and bending stiffness when compared to traditional Ilizarov circular external fixators. 28,29 This led to unwanted motion and the fracture site with resultant loss of reduction, non-union and increased pin-site infection rates. [30][31][32][33][34] Conventional circular external fixation, however, has recently emerged as a viable treatment alternative for bicondylar plateau fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical analysis also demonstrated that the use of four tensioned olive wires combined with a single lag screw provided adequate stability when compared to dual plating. 28 The aim of this study was to compare the complication and union rate of tibial plateau fractures treated by circular external fixation in patients older than 55 years with that achieved in younger patients. While we would like to believe that a 55-year-old person should not be classified as elderly, we used this figure as it is in line with previously published reports.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the FEA in the present study can be used to verify the analytical solutions as given in §3. Watson et al (2000Watson et al ( , 2003b have published the results from their experimental work for displacements of a K-wire (DZ180 mm and dZ1.8 mm) loaded perpendicular to its longitudinal axis at its midpoint, under different pretensions, in two graphs ( fig. 5 of Watson et al 2000Watson et al , 2003b.…”
Section: Discussionmentioning
confidence: 99%
“…Watson et al (2000Watson et al ( , 2003b have published the results from their experimental work for displacements of a K-wire (DZ180 mm and dZ1.8 mm) loaded perpendicular to its longitudinal axis at its midpoint, under different pretensions, in two graphs ( fig. 5 of Watson et al 2000Watson et al , 2003b. The results in figure 8 of this paper, which are based on the analytical solutions, are comparable with the results shown in either of those graphs.…”
Section: Discussionmentioning
confidence: 99%
“…The ideal characteristics of a ring fixator with ability to accomodate variable stiffness to optimize the healing process at all stages of treatment should according to Watson et al (2000) be:…”
Section: External Fixatormentioning
confidence: 99%